Chapter 9. Leafy Vegetable Production - Germán Sandoya-Miranda; Ramdas Kanissery; Nicholas S. Dufault; Johan Desaeger; Anna Meszaros; julien Beuzelin; Katia Viana Xavier (EDIS, 2024)
Chapter 9 of the Vegetable Production Handbook of Florida